Nanofiber-reinforced decellularized amniotic membrane improves limbal stem cell transplantation in a rabbit model of corneal epithelial defect. (1st October 2019) - Zhou, Zhengbing; Long, Da; Hsu, Chih-Chien; Liu, Huanhuan; Chen, Long; Slavin, Benjamin; Lin, Hui; Li, Xiaowei; Tang, Juyu; Yiu, Samuel; Tuffaha, Sami; Mao, Hai-Quan
Graphical abstract: Abstract: Human amniotic membrane (AM) offers unique advantages as a matrix to support the transplantation of limbal stem cells (LSCs) due to its inherent pro-regenerative and anti-inflammatory properties. However, the widespread use of AM in clinical treatments of ocular surface disorders is limited by its weak mechanical strength and fast degradation, and high cost associated with preserving freshly isolated AM. Here we constructed a composite membrane consisting of an electrospun bioabsorbable poly(ε-caprolactone) (PCL) nanofiber mesh to significantly improve the ultimate tensile strength, toughness, and suture retention strength by 4–10-fold in comparison with decellularized AM sheet. The composite membrane showed extended stability and conferred longer-lasting coverage on wounded cornea surface compared with dAM. The composite membrane maintained the pro-regenerative and immunomodulatory properties of dAM, promoted LSC survival, retention, and organization, improved re-epithelialization of the defect area, and reduced inflammation and neovascularization. This study demonstrates the translational potential of our composite membrane for stem cell-based treatment of ocular surface damage. Statement of Significance: Human decellularized amniotic membrane (dAM) has been widely shown as a biodegradable and bioactive matrix for regenerative tissue repair. However, the weak mechanical property has limited its widespread use in the clinic. Here we constructed a composite membrane using a layer of electrospun poly(ε-caprolactone) (PCL) nanofiber mesh to reinforce the dAM sheet through covalent interfacial bonding, while retaining the unique bioactivity of dAM. In a rabbit model of limbal stem cell (LSC) deficiency induced by alkaline burn, we demonstrated the superior property of this PCL-dAM composite membrane for repairing damaged cornea through promoting LSC transplantation, improving re-epithelialization, and reducing inflammation and neovascularization. This new composite membrane offers great translational potential in supporting stem cell-based treatment of ocular surface damage.